The genetics of the horse [ - Bowling, Anne T.; Ruvinsky, Anatoly (CABI, 2000)
The theory and application of mammalian genetics has evolved rapidly in the 1980s and 1990s, giving scientists insight into the biological processes which affect the functions of the animal in question. This title is a comprehensive review of research i horse genetics.